Institutution for limited proprietary rights in scientific works of Kyiv Law Society (Second half of the XIX century) - Pylypchuk, O. O. (History of science and technology, 2018)
The article highlights the contribution of scientists of the Kyiv Law Society to solving the problems of licit land tenure in the second half of the nineteenth century, which was an example of the Institutution of limited real rights, which is also called the right to other people’s things. In the historical context, the basic principles of the activity of the rents law in the Ukrainian lands are reflected, where it was very popular since the fifteenth century and until the end of the nineteenth century, and it was shown that the rents land tenure was for a long time the right to inherit possession and disposal of land belonging to the private owner, for which the latter received an annual unchanging payment – rents. The main stages of the emergence and development of the rents legal relations from the time of the Lithuanian-Ruskoi state and up to the last decades of the existence of the Russian Empire have been considered. It is shown how in the various historical periods at the legislative level, the actual legal relations were maintained in the most important normative legal acts that acted on the territory of modern Ukraine. The main changes in this issue after 1840 are shown, when on the Ukrainian lands the Lithuanian statute was abolished and the Code of Laws of the Russian Empire was introduced, which banned the rents legal relationship. That also led to a number of problems, because Rents land tenure after 1840 was no longer legal regulation. It was traced as members of the Kyiv Law Society raised this issue and initiated its decision at the legislative level. The analysis of scientific works of the members of the Kyiv Law Society has been carried out, which showed that the development of the economy in the conditions of capitalist relations in the second half of the nineteenth century led to the fact that the existing legal relations became unfavorable for landowners. Therefore, they tried to resolve the problem for several decades by their efforts in a situation that required the implementation of a large-scale reform, transferring the existing legal relations to the term lease. The contribution of the members of the KLS to the implementation of the actual reform, in particular, in the work on the "Regulations on the land structure of village perpetual rents in the provinces of West and Biloruskykh" in 1886, which finally abolished the rents legal relations and began the transformation of civil legal relations between large landowners and former rents owners who lived on the lands of the latter, in the conditions of the new socio-economic realities of the country.